3D visualization of dislocation arrangement using scanning electron microscope serial sectioning method. (May 2015) - Yamasaki, S.; Mitsuhara, M.; Ikeda, K.; Hata, S.; Nakashima, H.
Abstract : We performed the three-dimensional visualization of dislocations through serial sectioning and use of SEM electron channeling contrast (ECC) images for a crept nickel-based alloy. We successfully reconstructed a volume of approximately 7.5 μm 3, including dislocation arrangements, by performing calculations based on the continuous tomograms of ECC images. By incorporating the information on crystal orientation obtained by the electron back-scattered diffraction, we verified that the three-dimensional arrangement of dislocations, such as slip plane, was accurately reflected in the three-dimensional volume.